What's the point of tobacco control? Comment on Dan Halliday, ‘The ethics of a smoking licence’ - Voigt, Kristin (Journal of medical ethics, 2016)
Sales taxes have become a central feature of antismoking initiatives across the world. Dan Halliday provides a strong argument in favour of smoking licences as an alternative to such taxes.1 I agree with much of his argument. For this commentary, I want to take a cue from Halliday's points about the relationship between ideal and non-ideal theory. In particular, I want to take a step back to consider on what basis we should assess the relative merits of different antismoking interventions such as taxes and licences and, more broadly, what the goal of tobacco control and antismoking initiatives should be. While this may at first glance seem obvious—the goal, one might argue, is to reduce smoking as much as possible and, ideally, to eradicate it entirely—such a response would, I think, be too quick. Much is to be gained from considering in more detail what the goals of tobacco would be if we could abstract from, or ‘assume away’, certain aspects of the real world, before considering how these goals might need to be adapted in light of real world constraints.Halliday emphasises that his argument is an exercise in non-ideal theory. In particular, it addresses real world problems that, if we were arguing at the level of ideal theory, we would assume do not exist. However, Halliday leaves open what response would be required to smoking from the perspective of ideal theory, noting that while some ideal societies might ban tobacco altogether, others might not restrict it at all (ref. 1, p. 1).The general case for a licence, Halliday suggests, is that it imposes upfront substantial costs on an activity the implicit costs and risks of which would not otherwise materialise until much further in the future. Drawing on …